Pemanfaatan media sosial online dan strategi konten untuk meningkatkan pemasaran UMKM ESM collection - Sri Suhandiah; Aprilia Aryanti Widyasari (Universitas Pendidikan Indonesia (UPI), 2021)
Covid-19 pandemic not only strike people health, but it also affects the economic aspect. The pandemic also hit the MSMEs, especially ESM Collection, which have decreasing selling due to it only running in the offline store. Not having online marketing media, lack of skill and knowledge in utilizing social media for marketing strategy are the main issues that ESM Collection faces. This community service activity aims to help ESM Collection to overcome its difficulties. Those issues were solved through training and mentoring in using social media Instagram to do online marketing and content marketing strategy. This event is divided into three steps. Firstly, is developing a training guidebook, secondly training to use the marketing application and evaluate it. Lastly is mentoring. Instagram training is given to ESM Collection staff in two days, and mentoring is one month. The result of this event is the guidebook helps the participants to follow the training, and the training method can increase their knowledge to use Instagram as marketing media. Furthermore, through mentoring participants can upgrade their skill to implementing content strategy on Instagram. All in all, ESM Collection now can utilize Instagram as their online marketing media to apply the content marketing strategy to widen their market and increase their sales.